2020
DOI: 10.1021/acsnano.0c04522
|View full text |Cite
|
Sign up to set email alerts
|

Remotely Triggered Liquefaction of Hydrogel Materials

Abstract: Adaptable behavior such as triggered disintegration affords a broad scope and utility for (bio)materials in diverse applications in materials science and engineering. The impact of such materials continues to grow due to the increased importance of environmental considerations as well as the increased use of implants in medical practices. However, examples of such materials are still few. In this work, we engineer triggered liquefaction of hydrogel biomaterials in response to internal, localized heating, media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Moreover, it can also remove anions and cations and organic pollutants in dye wastewater. Very meaningful research results including remote liquefaction (Figure 6(a)) [127], molecular ink [128], contact lens sensor [129], and so on [130][131][132][133] are also reported. As a biocompatible polymer, PVA-based hydrogels prepared with bimetallic ions as crosslinking agents have high water retention properties, excellent mechanical strength, and self-healing properties and have also been studied for artificial skin and wearable sensor devices (Figure 6(b)) [120,134].…”
Section: 42mentioning
confidence: 79%
“…Moreover, it can also remove anions and cations and organic pollutants in dye wastewater. Very meaningful research results including remote liquefaction (Figure 6(a)) [127], molecular ink [128], contact lens sensor [129], and so on [130][131][132][133] are also reported. As a biocompatible polymer, PVA-based hydrogels prepared with bimetallic ions as crosslinking agents have high water retention properties, excellent mechanical strength, and self-healing properties and have also been studied for artificial skin and wearable sensor devices (Figure 6(b)) [120,134].…”
Section: 42mentioning
confidence: 79%
“…The change in temperature can control the gel-sol transformation of thermosensitive hydrogels and release active factors for enhanced therapy [ 35 ]. Pedersen et al reported that a polyvinyl alcohol/gold nanorod (AuNR) hydrogel was heated to <50 °C under NIR irradiation and liquefied in 15–20 s, and the pulsed release model cargo of fluorescein isothiocyanate controlled by NIR irradiation was realized successfully [ 36 ]. Under NIR irradiation, [poly( d , l -lactide)-poly(ethylene glycol)-poly( d , l -lactide)/black phosphorus (BP) hydrogel undergo a sol-gel transition at 46.5 °C after only 20 s [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach in developing “smart’ multiresponsive hydrogels is via the incorporation of temperature-sensitive additives, such as liposomes or nanoparticles ( Lu and Ten Hagen, 2020 ; Palmese et al, 2020 ). Recently, Pedersen et al (2020) developed hydrogel biomaterials with triggered liquefaction in response to internal, localized heating, mediated by near-infrared light as external stimulus. This adaptable behavior was obtained by combining poly(vinyl alcohol) hydrogel with gold nanoparticles or an organic photothermal dye as heat generators.…”
Section: Strategies For Porous Scaffold Bioactivation By Drug Entrapment and Deliverymentioning
confidence: 99%
“…This adaptable behavior was obtained by combining poly(vinyl alcohol) hydrogel with gold nanoparticles or an organic photothermal dye as heat generators. Upon laser light irradiation, composite hydrogel underwent liquefaction within seconds allowing the controlled, on-demand release of the incorporated cargo ( Pedersen et al, 2020 ).…”
Section: Strategies For Porous Scaffold Bioactivation By Drug Entrapment and Deliverymentioning
confidence: 99%